Forensic Computer Crime Investigation - Johnson, Thomas (CRC Press, 2009)
The Digital Age offers many far-reaching opportunities - opportunities that allow for fast global communications, efficient business transactions…and stealthily executed cyber crimes. Featuring contributions from digital forensic experts, the editor of Forensic Computer Crime Investigation presents a vital resource that outlines the latest strategies law enforcement officials can leverage against the perpetrators of cyber crimes.